DNA damage invokes mitophagy through a pathway involving Spata18. Issue 12 (26th May 2020) - Dan, Xiuli; Babbar, Mansi; Moore, Anthony; Wechter, Noah; Tian, Jingyan; Mohanty, Joy G; Croteau, Deborah L; Bohr, Vilhelm A
Abstract: Mitochondria are vital for cellular energy supply and intracellular signaling after stress. Here, we aimed to investigate how mitochondria respond to acute DNA damage with respect to mitophagy, which is an important mitochondrial quality control process. Our results show that mitophagy increases after DNA damage in primary fibroblasts, murine neurons and Caenorhabditis elegans neurons. Our results indicate that modulation of mitophagy after DNA damage is independent of the type of DNA damage stimuli used and that the protein Spata18 is an important player in this process. Knockdown of Spata18 suppresses mitophagy, disturbs mitochondrial Ca 2+ homeostasis, affects ATP production, and attenuates DNA repair. Importantly, mitophagy after DNA damage is a vital cellular response to maintain mitochondrial functions and DNA repair.